The Ottoman Approach to Scientific Classification in Tafsir History: A Study of Taskopruluzade Ahmad Efendi’s ‘Miftâhu’s-Saâde’ - Hariani, Hidayah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
This study presents an analytical investigation of the historical aspect of tafsir within the Ottoman tradition, as found in the literary composition "Miftāhus-Sa'âda," which was authored by Taskopruluzade (d. 968/1561). This work holds a significant role in the classification of knowledge, serving as the foundational underpinning for the establishment of scientific traditions within the Ottoman Empire. Through the lens of this work, the historical narrative of tafsir is recontextualized to align with the scientific framework inherent in the Ottoman tradition, thus imparting a distinctive character to the realm of Qur'anic interpretation during the Ottoman Empire's tenure. Employing historical research methodologies encompassing heuristics, verification, interpretation, and historiography, this investigation critically examines the history of scientific classification, a bedrock for shaping the taxonomy of categorized disciplines within their respective contexts. The research delves deeply into the composition of "Miftâhu’s-Saâde," offering a comprehensive perspective on the evolution of tafsir history. The findings of this research underscore that, in the process of Science Classification congruent with the scientific ethos of the Ottoman Empire, Taskopruluzade, within "Miftâhu’s-Saâde," undertakes three pivotal tasks. Firstly, he evaluates classical tafsir works through the lens of scientific classification norms entrenched in the Ottoman tradition. Secondly, these appraised tafsir works are juxtaposed with others, facilitating the establishment of benchmarks and taxonomies that wield considerable influence in guiding the trajectory of tafsir history. Thirdly, a comprehensive exploration ensues into the interplay between interpretive works and the activities of interpretation. The implications of this discourse offer a substantive contribution, deepening the comprehension of tafsir history and the classification of knowledge within the scholarly milieu of the Ottoman Empire.